2018
DOI: 10.1111/vde.12661
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the secretion of antimicrobial peptides and antimicrobial effect of skin wash in atopic and healthy dogs: a preliminary study

Abstract: This study found no difference in AMP secretion levels between healthy and nonlesional atopic canine skin. However, a significantly lower antimicrobial activity was present in the skin washes from atopic compared to healthy skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 24 publications
(47 reference statements)
0
24
0
Order By: Relevance
“…The choice of using a concentration of 1 µg/mL HDP was based on previous in vitro and in vivo studies. 15,16,18,[20][21][22] Such studies showed an amount of ≤0.4 µg/mL HDPs secreted in the skin wash of healthy and atopic dogs. 22 However, because of the increased adhesion of HDPs to the stratum corneum demonstrated in canine skin, 21 the amount of HDPs is likely to be greater than the one secreted in skin washes.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The choice of using a concentration of 1 µg/mL HDP was based on previous in vitro and in vivo studies. 15,16,18,[20][21][22] Such studies showed an amount of ≤0.4 µg/mL HDPs secreted in the skin wash of healthy and atopic dogs. 22 However, because of the increased adhesion of HDPs to the stratum corneum demonstrated in canine skin, 21 the amount of HDPs is likely to be greater than the one secreted in skin washes.…”
Section: Discussionmentioning
confidence: 98%
“…15,16,18,[20][21][22] Such studies showed an amount of ≤0.4 µg/mL HDPs secreted in the skin wash of healthy and atopic dogs. 22 However, because of the increased adhesion of HDPs to the stratum corneum demonstrated in canine skin, 21 the amount of HDPs is likely to be greater than the one secreted in skin washes. Finally, the MIC/MBC of cBD103 and cCath for methicillin-resistant SP has been found to be ˜25 µg/mL, 20 a much greater concentration than those recovered in skin washes.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations